2018
DOI: 10.1016/j.pss.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Background and lunar neutron populations detected by LEND and average concentration of near-surface hydrogen near the Moon's poles

Abstract: Neutron flux measurements by the Lunar Exploration Neutron Detector (LEND) on the Lunar Reconnaissance Orbiter (LRO) enable quantifying hydrogen-bearing volatiles in the lunar surface from orbit. Accurately determining hydrogen abundance requires discriminating between the instrument background detection rate and the population of lunar-sourced neutrons that are sensitive to surficial hydrogen. We have investigated the detection rate for lunar and non-lunar (spacecraft-sourced) neutrons in LEND by modeling map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a direct response to the raised concerns by Lawrence et al (2011) and Mitrofanov et al (2011) presented additional evidence supporting their earlier results. Later studies (Litvak et al, 2012(Litvak et al, , 2016Livengood et al, 2018) could show further that LEND indeed measures a significant amount of collimated epithermal neutrons and represents an appropriate data set to be used for mapping hydrogen at higher spatial resolution than was possible with LPNS (Litvak et al, 2012). Therefore, we decided to use the previously published LEND data (Sanin et al, 2017) to carry out the presented analysis.…”
Section: 1029/2020je006598 2 Of 27mentioning
confidence: 99%
“…In a direct response to the raised concerns by Lawrence et al (2011) and Mitrofanov et al (2011) presented additional evidence supporting their earlier results. Later studies (Litvak et al, 2012(Litvak et al, , 2016Livengood et al, 2018) could show further that LEND indeed measures a significant amount of collimated epithermal neutrons and represents an appropriate data set to be used for mapping hydrogen at higher spatial resolution than was possible with LPNS (Litvak et al, 2012). Therefore, we decided to use the previously published LEND data (Sanin et al, 2017) to carry out the presented analysis.…”
Section: 1029/2020je006598 2 Of 27mentioning
confidence: 99%
“…Using estimates of mare basalt unit ages (e.g., Hiesinger et al, 2011) and thicknesses (Weider et al, 2010), Needham and Kring (2017) concluded that during a period of peak mare emplacement and volcanic volatile release at ∼3.5 Ga (supporting information Figures S1a and S1b), the maximum atmospheric pressure at the lunar surface could have reached ∼1 kPa (∼1.5 times greater than the current atmospheric surface pressure of Mars) ( Figure S1c) and that this lunar atmosphere could have persisted for ∼70 million years before fully dissipating ( Figure S1c). They further pointed out that even though most of the volcanically released volatiles will have been lost to space, if only 0.1% of the water released during these eruptions migrated to the permanently shadowed polar regions of the Moon, then the resulting hydrogen mass could account for the entire currently observed hydrogen deposits located there (Eke et al, 2009;Livengood et al, 2018).…”
Section: Introductionmentioning
confidence: 99%